Linking Dynamic Water Storage and Subsurface Geochemical Structure Using High‐Frequency Concentration‐Discharge Records - Paul Floury; Julien Bouchez; Jennifer L. Druhan; Jérôme Gaillardet; Arnaud Blanchouin; Éric Gayer; Patrick Ansart (Water Resources Research)
Abstract Shifts in water fluxes and chemical heterogeneity through catchments combine to dictate stream solute export from the Critical Zone. The ways in which these factors emerge in resultant concentration‐discharge (C‐Q) relationships remain obscure, particularly at the timescale of individual precipitation and discharge events. Here we take advantage of a new high‐frequency, multi‐element and multi‐event stream C‐Q data set. The stream solute concentrations of seven major ions were recorded every 40 min over five flood events spanning one hydrologic year in a French agricultural watershed (Orgeval) using a lab‐in‐the‐field deployment we refer to as a “River Lab.” We focus attention on the recession periods of these events to consider how geochemical heterogeneity within the catchment translates into dynamic stream solute concentrations during shifts in water storage. We first show that for C‐Q relationships resulting from data acquisition over multiple flood events, lumping all trends together can lead to biases in characteristic C‐Q parameters. We then reframe C‐Q relationships using a simple recession curve analysis to consider how hydrological processes produce chemical mixing of distinct solute pools immediately following discharge events. We find three distinct classes of behavior among the major solutes, none of which can be interpreted based on water storage changes alone. The shape of C‐Q relationships for each solute can then be related to their vertical zonation in the subsurface of Orgeval, and to the capacity for subcomponents of these distributions to be readily mobilized during a discharge event.